Analisis Kuantitatif Dampak Intensitas Komunikasi Politik terhadap Partisipasi Politik Aktif Etnis Tionghoa di DKI Jakarta - Pratama, Muhammad Iqbal; Qotni, Imam Darul; R, Muhammad Ferdi; Nugraha, Akbar Fari (CV. ITTC INDONESIA, 2024)
explores the complexity of Jakarta's political landscape influenced by ethnic diversity, with a focus on the significant role of Ethnic Chinese in the city's political dynamics. Taking ethnic diversity as a foundation, this research aims to investigate the intensity of ethnic Chinese political communication and its impact on public perception and political participation in Jakarta. Understanding the dynamics of political communication is becoming increasingly important, given the potential for governments and politicians to capitalize on this diversity through appropriate approaches, creating more inclusive and multicultural political contestation. This research emphasizes intercultural communication, communication psychology, and media influence on public policy. In particular, it explores public perceptions of Ethnic Chinese political communication and how political messages are understood by Jakarta's diverse communities. The analysis also covers levels of political participation, including involvement in elections and contributions to political organizations.